Base catalyzed transesterification of acid treated vegetable oil blend for biodiesel production - Yusup, Suzana (Elsevier, 2010)
Biodiesel can be produced from low cost non-edible oils and fats. However, most of these sources are of high free fatty acid content which requires two stage transesterification to reduce the acid value and produce biodiesel. The acid treatment step is usually followed by base transesterification since the latter can yield higher conversions of methyl esters at shorter reaction time when compared with acid catalyzed reaction. In the current study, base transesterification in the second stage of biodiesel synthesis is studied for a blend of crude palm/crude rubber seed oil that had been characterized and treated with acid esterification. Optimum conditions for the reaction were established and effect of each variable was investigated. The base catalyzed transesterification favored a temperature of 55 C with methanol/oil molar ratio of 8/1 and potassium hydroxide at 2% (ww1) (oil basis). The conversion of methyl esters exceeded 98% after 5 h and the product quality was verified to match that for biodiesel with international standards.